PENGARUH RASIO LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Srimayanti, Depi; Efriyenti, Dian (LPPM Universitas Putera Batam, 2020)
Financial distress is a state of a company that is experiencing financial difficulties before bankruptcy. very important in monitoring company finances, because before the company goes bankrupt, it will definitely experience monetary difficulties. This study aims to determine the effect of liquidity, profitability and leverage on financial difficulties. The object of this research is the consumer goods sector companies listed on the Indonesia Stock Exchange. The population of this study consisted 49 companies in the 2015-2019 period. The sampling technique in this study uses a porposive sampling method and gets 36 samples that meet the criteria. The data used are secondary data in the form of financial statements obtained from the Indonesia Stock Exchange. The analytical method used in this study is logistic regression analysis which is processed using SPSS. The results of this study prove the current ratio of debt to asset ratio and return on assets simultaneously affect financial difficulties. while current assets and debt to asset ratios have no effect and are not significant to financial difficulties, while the variable return on assets has a negative and significant effect on financial difficulties.